RNA-Sequencing approach for exploring the therapeutic effect of umbilical cord mesenchymal stem/stromal cells on lipopolysaccharide-induced acute lung injury - Cui, Enhai; Zhang, Luwen; Pan, Xin; Zhang, Qiang; Zhang, Ling; Wu, Feifei; Chen, Na; Lv, Lu; Chen, Wenyan; Chen, Hong; Lin, Aifu; Wang, Feng; et al. (Frontiers in Immunology, 2022)
Acute lung injury (ALI) is significantly associated with morbidity and mortality in patients with critical diseases. In recent years, studies have identified that mesenchymal stem/stromal cells (MSCs) ameliorate ALI and pulmonary fibrosis. However, the mechanism underlying this outcome in ALI has not yet been investigated. In this study, RNA sequencing technology was used to analyze the gene expression profile of lung tissue in lipopolysaccharide (LPS)-induced ALI rats following treatment with human umbilical cord MSC (HUCMSC). Differential expression analyses, gene ontology annotation, Kyoto Encyclopedia of Genes and Genomes enrichment, protein–protein interaction network identification, and hub gene analysis were also performed. HUCMSC treatment decreased inflammatory factor production and alveolar exudates, and attenuated lung damage in LPS-induced ALI rats. The RNA-Seq data indicated that HUCMSC treatment activated the IL-17, JAK-STAT, NF-κB, and TNF-α signaling pathways, increased oxygen transport, and decreased extracellular matrix organization. HUCMSC exert beneficial effects on ALI via these signaling pathways by reducing inflammation, inhibiting pulmonary fibrosis, and improving lung ventilation. Moreover, our study further revealed the hub genes (Tbx2, Nkx2-1, and Atf5) and signaling pathways involved in HUCMSC treatment, thus providing novel perspectives for future research into the molecular mechanisms underlying cell treatment of ALI. HUCMSC can regulate multiple genes and signaling pathways, which can prevent LPS-induced lung damage in an ALI rat model.